Đánh giá của người sử dụng lao động về chất lượng đào tạo cử nhân ngành Luật tại Học viện Tòa án - Đặng Thị Thơm, Đặng Thị Thơm; Nguyễn Thị Minh, Nguyễn Thị Minh; Nguyễn Thị Kiều Trinh, Nguyễn Thị Kiều Trinh (Tạp chí Giáo dục, 2025)
In the context of judicial reform and international integration, improving the quality of legal human resources has become an urgent requirement, making employer-based evaluation of university training quality increasingly significant. The article introduces the results of research on the assessment of the quality of university training from the perspective of employers through the collection and analysis of opinions and comments of employers on the quality of bachelor of law training at the Academy of Justice. The research results from employers aim to evaluate the training quality of the Academy of Justice as well as the level of meeting the practical requirements of the training program. The evaluation is carried out based on the criteria proposed by the author in accordance with the output standards of the training program. Based on the analysis of the causes and current situation, the article proposes some innovations in program content, teaching methods as well as assessment and evaluation to improve the training quality and meet the requirements of employers.